The Implementation of the Canons on Mass Offerings in Particular Law and Custom with Special Reference to the Dioceses of Cameroon - Ndey, Francis (Université Saint-Paul / Saint Paul University, 2019)
The immemorial practice of the institute of Mass offerings and its reaffirmation in the present universal law of the Church presents several canonical problems, especially with the proper implementation and application of the canons on Mass offerings in particular law and the customs of particular Churches. This work explores the historical origins and development, the theological understanding and the practice of the Mass offering system within the Church, with the view of a proper and equitable application of the canons on Mass offerings within the customs and particular law of particular Churches in Cameroon. It develops the proper interpretation and application of the canons on Mass offerings in particular law. The first chapter considers the historical origins and evolution of the practice of Mass offerings. The introduction of monetary transactions within Eucharistic praxis influenced the development of an economic theology of the fruits of the Mass. The pastoral practice of the limitation of the application of the fruits of the Mass to one Mass offering donor, to the exclusion of others, had the consequent theological effect of introducing the language of economics and commerce in the conceptualization of Eucharistic theology and efficacy of the Mass. The second chapter presents a systematic exposure and analysis of the scope of canonical doctrine in actual legislation governing Mass offerings, analyzed in light of the 1917 Code, the 1974 motu proprio Firma in traditione, and the decree Mos iugiter on “pluri-intentional” Masses. This chapter accentuates the right of the priest celebrant with regard to the Mass offering, a grant of the universal law of the Church, while also underscoring the complete and total exclusion of any semblance of trafficking or commerce within the Mass offering transaction. The third chapter addresses the issue of simony and the various juridical theories devised to justify the practice of Mass offerings and the avoidance of all charges of simony. The fourth and final chapter focuses on the implementation and application of the canons on Mass offerings in particular law and customs within the dioceses of Cameroon. In light of the assessment of some questionable practices within some the dioceses in Cameroon, we have proposed a uniform praxis based on sound canonical principles that if prudently and equitably applied within the dioceses of Cameroon will eliminate questionable and unorthodox practices.
Keywords: Mass offering; Customs; Catholism; Theology